Occurrence and characteristics of microplastics in the coral reef, sea grass and near shore habitats of Rameswaram Island, India. (November 2020) - Jeyasanta, K. Immaculate; Patterson, Jamila; Grimsditch, Gabriel; Edward, J.K. Patterson
Abstract: This study compares the occurrence and characteristics of microplastics (MPs) and heavy metal contaminants in the water and sediment of three habitats (corals, seagrass-beds and near-shores) of Rameswaram Island, India. The overall mean concentration of MPs varies from 24 ± 9 to 96 ± 57 items/L in water, and from 55 ± 21 to 259 ± 88 items/kg in sediment. The value of abundance is the greatest in the coral reef site CR-1 (96 ± 51 items/L; 259 ± 88 items/kg) followed by the seagrass site SG-2 (94 ± 55 items/L; 203 ± 75 items/kg) and the near-shore site St-15 (95 ± 63 items/L; 193 ± 75 items/kg). PE fiber (<1000 μm) is predominant in water, whereas PP fiber and fragment (between 2000 and 5000 μm) dominate the sediment. The SEM images of MPs reveal features which are characteristic of degradation like surface roughness, cracks, protrusions, and chalking, along with surface precipitates of both chemical and biological origin. EDAX images show the presence of Cr, Fe, Hg, Pb, Cu, As and Cd associated with MP surfaces. Graphical abstract: Unlabelled Image Highlights: Mean MPs ranges from 24±9 to 96±57 items/L in water, and 55±21 to 259±88 items/kg in sediment. Fibers of size<1000μm, fibers and fragments with 2000 - 5000μm predominant in water and sediment. The predominant polymer type in surface water is PE and that in sediment is PP. SEM image shows complex surface morphology of MPs, and EDAX indicates that most MPs contain metals. ICP-MS results reveal MPs act as carriers of trace elements, which is threat to marine species.